2003
DOI: 10.2105/ajph.93.9.1471
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Housing: A Structured Review of Published Evaluations of US Interventions to Improve Health by Modifying Housing in the United States, 1990–2001

Abstract: We sought to characterize and to evaluate the success of current public health interventions related to housing. Two reviewers content-analyzed 72 articles selected from 12 electronic databases of US interventions from 1990 to 2001. Ninety-two percent of the interventions addressed a single condition, most often lead poisoning, injury, or asthma. Fifty-seven percent targeted children, and 13% targeted seniors. The most common intervention strategies employed a one-time treatment to improve the environment; to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(62 citation statements)
references
References 43 publications
0
62
0
Order By: Relevance
“…We often become tangled in circular explanations as we attribute the 414 SHAW effects of poverty on health to poor housing, and the effects of poor housing on health to general poverty. Contemporary interventions to improve health by modifying housing, and evaluation of those interventions, are similarly fraught with conceptual and methodological challenges (67). This difficulty of disentangling and proving causal links is inherent to the study of social determinants of health, which tend to be multifaceted and confounded.…”
Section: Conclusion: Housing Public Health and Povertymentioning
confidence: 99%
“…We often become tangled in circular explanations as we attribute the 414 SHAW effects of poverty on health to poor housing, and the effects of poor housing on health to general poverty. Contemporary interventions to improve health by modifying housing, and evaluation of those interventions, are similarly fraught with conceptual and methodological challenges (67). This difficulty of disentangling and proving causal links is inherent to the study of social determinants of health, which tend to be multifaceted and confounded.…”
Section: Conclusion: Housing Public Health and Povertymentioning
confidence: 99%
“…In addition, the percentage of households seeking medical care for their child's asthma substantially decreased for each of our three measures: emergency department visits, Previous studies have demonstrated that effective healthy homes intervention programs require multiple home visits. 7,[17][18][19][20][21] We designed our program on this premise, and staff made four in-home visits with most of the participating households. One key to program success that studies have cited is the effectiveness of outreach workers.…”
Section: Discussionmentioning
confidence: 99%
“…The most successful programs are those that have combined environmental interventions with face-to-face education over multiple home visits. 7,[17][18][19][20][21] …”
mentioning
confidence: 99%
“…In addition, devices which are affordable and easy to use may be more likely to be used and therefore increase effectiveness (Saegert et al, 2003).…”
Section: Interventions To Reduce Unintentional Injuries Fires and Fmentioning
confidence: 99%
“…Many countries have successfully invested heavily in lead reduction (Saegert et al, 2003;Guilart et al, 2003) but exposure to lead in some countries remains a common domestic hazard with significant health impacts, those most at risk are low income groups living in poor housing (Canfield et al, 2003;Margai, Henry, 2003;Leighton et al, 2003;Prüss-Üstün et al, 2003). Adverse physical, mental, intellectual and developmental effects have been associated with lead exposure even at low levels of exposure (Lanphear et al, 2005).…”
Section: Interventions To Reduce Leadmentioning
confidence: 99%